2017
DOI: 10.3949/ccjm.84a.15144
|View full text |Cite
|
Sign up to set email alerts
|

Imaging suggestive, but symptoms atypical

Abstract: FIGURE 1. Computed tomography showed increased attenuation in the ambient cistern (black arrow) and cortical sulci (white arrow).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…CPR training is a major part of medical courses, but the most effective method of training is still unclear and depends on trainees' groups and previous theoretical knowledge of CPR among them. Although the importance of BLS, studies has shown that these skills are not acquired sufficiently6 . Acquisition of BLS skills can be difficult.…”
mentioning
confidence: 99%
“…CPR training is a major part of medical courses, but the most effective method of training is still unclear and depends on trainees' groups and previous theoretical knowledge of CPR among them. Although the importance of BLS, studies has shown that these skills are not acquired sufficiently6 . Acquisition of BLS skills can be difficult.…”
mentioning
confidence: 99%